Utilization and Characterization of Oyster Shell as Chitosan and Nanochitosan - Lia Handayani; Faisal Syahputra; Yayuk Astuti (Jurnal Kimia Sains dan Aplikasi, 2018)
Oyster is one of bivalve groups widely consumed by human, thus, it results in producing huge waste shells affecting the environment. One way to increase the value of oyster shells is to process them into chitosan. This study aims to isolate chitin then synthesize it into chitosan and convert chitosan into nano-sized chitosan and analyze the characteristics. The steps to produce chitosan from waste shells included demineralization using HCl 1 N and deproteinization using NaOH 3%. The next step was to convert chitin into chitosan through a deacetylation process using NaOH 50%. After chitosan was formed, it was continued to convert chitosan into nano chitosan particles using ion gelation method with the addition of surfactant (tween 80) and crosslinker (TPP 0.1% and 0.5%). The results showed that yield of transformation chitin into chitosan was 61.1%. Meanwhile, the yield calculated from initial weight of raw material was 18.33% with deacetylation degree value equal to 89.14%. Based on morphological analysis using SEM, the size of chitosan particles was not distributed homogeneously that was in the range of 892 nm-1.54 μm, while the nano chitosan particle size obtained was uniformly formed in the range of 679 nm-910 nm.